Human Immune System Reconstitution in NOD/Shi-Prkdcscid Il2rgem1/Cyagen Mice to Study HIV Infection: Challenges and Pitfalls - Aleksey M. Nagornykh; Marina A. Tyumentseva; Aleksandr I. Tyumentsev; Leonid A. Fedotov; Konstantin S. Karbyshev; Evgeniya A. Orlova; Liliia N. Volchkova; Lubov S. Danilova; Andrey S. Akinin; Vasiliy G. Akimkin (Life)
The main challenge after engraftment of human tissues to mice is the development of graft-versus-host disease. It often occurs in an acute form, which reduces the time frame for observations. This is especially important to take into account when planning long-term studies of chronic diseases such as HIV infection. In addition, in mice, even with a similar genotype but different origin, the interaction between the graft and the recipient’s organism can manifest itself differently. We engrafted human immune cells in three different concentrations into immunodeficient NOD/Shi-Prkdcscid Il2rgem1/Cyagen mice. Then, the initial points of development of a severe graft-versus-host reaction and the maximum possible time window for humane observation were determined. The study included regular complete blood count and the monitoring of the dynamics of the concentration of human cells in the blood of mice. In addition, the effect of grafts on the activation of the recipient’s immune system was assessed. Finally, necropsy and histological and immunohistochemical examinations of the organs were performed to determine the localization of human cells. In this way, critical factors determining the success of human immune system reconstitution in mice were identified.